Tinjauan Literatur Faktor – Faktor yang Berhubungan dengan Kepatuhan Pengunaan Helm pada Remaja Saat Berkendara Menurut Theory of Planned Behavior (TPB) - Nasywa Safitri; Luqman Effendi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Traffic accidents are the leading cause of death among teenagers aged 15 years and above, with Indonesian National Police traffic data recording that motorcycles are involved in 72.42% of all cases. Risky behavior such as not wearing SNI-standard helmets is a major cause of fatal head injuries in this age group. This study aims to analyze the factors that influence safe riding compliance among adolescents through a literature review based on the Theory of Planned Behavior (TPB). The research method used a literature review by searching for articles in the Google Scholar database published between 2020 and 2025 with the inclusion criteria of open access journals in Indonesian. Based on the analysis of the selected articles, it was found that all TPB components were correlated with safe riding behavior. Attitude was the most frequently studied variable (90%), but it was not always significant because it was influenced by environmental factors. Subjective norms derived from positive pressure from family and peers were proven to increase adolescents' motivation to comply. Meanwhile, perceived behavioral control emerged as the strongest and most consistent determinant (100% significant) because it is directly related to the skills and confidence of riders. Therefore, safety riding programs must be integrated with technical skills training and the creation of a safety culture in the social environment to strengthen intentions.